High-stakes English test preparation among Indonesian university graduates: A thematic analysis - Abidin, Azwar; Muthalib, Lian Mulyani; Akbar, Muhammad Ali (Institut Agama Islam Negeri Kendari, 2026)
While institutional coaching currently dominates the discourse on high-stakes English test preparation, existing literature consistently neglects the strategic complexities faced by a substantial population of candidates relying exclusively on autonomous self-study methodologies. To address this critical gap, this study utilizes self-determination theory and Vygotskian sociocultural frameworks to evaluate independent test preparation. Specifically, the study operationalizes these paradigms to interrogate the intrinsic motivation and self-regulated learning strategies of non-institutional candidates. Employing an interpretive qualitative design, the investigation utilizes thematic analysis to examine the recorded narratives of 27 diverse Indonesian university graduates. The extracted thematic findings demonstrate that successful independent candidates deploy asynchronous digital platforms to mediate comprehensible input. Rather than passively consuming information, these learners construct personalized zones of proximal development to substitute for formal peer scaffolding. Furthermore, the evidence suggests that maintaining deep intrinsic motivation remains essential for sustaining long-term autonomous preparation routines. This study theoretically extends established sociocultural paradigms into digital self-study environments.